Comparative study between dexmedetomidine and fentanyl for sedation during mechanical ventilation in post-operative paediatric cardiac surgical patients - S R Prasad; Parimala Prasanna Simha; A M Jagadeesh (Indian Journal of Anaesthesia, 2012)
Aims and Objectives: To compare the efficacy of sedation and time taken for extubation using dexmedetomidine and fentanyl sedation in post-operative paediatric cardiac surgical patients. Methods: A prospective randomized double-blind study involving 60 children undergoing open heart surgery was conducted. The patients were divided into two groups, each involving 30 patients. One group received fentanyl at 1 μg/kg/h (Group A) and the other received dexmedetomidine at 0.5 μg/kg/h (Group B) for post-operative sedation with intermittent rescue fentanyl 0.5 μg/kg bolus in either group as per requirement during suctioning. The efficacy of sedation was assessed using the Ramsay sedation score, paediatric intensive care unit sedation score and the tracheal suction score. The time taken for extubation from the stoppage of infusion was noted. Results: Haemodynamic parameters between the two groups were comparable. All sedation scores were comparable in the fentanyl and dexmedetomidine groups. Average time (in minutes) required for extubation was 131.0 (±51.06 SD) in the dexmedetomidine group compared with 373.0 (±121.4 SD) in the fentanyl group. The difference in mean time for extubation was statistically significant. Conclusions: Dexmedetomidine facilitates adequate sedation for mechanical ventilation and also early extubation as compared with fentanyl.